The Oriental genus Nasimyia (Diptera: Stratiomyidae): Geographical distribution, key to species and descriptions of three new species - Yang, Zai-Hua; Hauser, Martin; Yang, Mao-Fa; Zhang, Ting-Ting (Zootaxa, 2013)
In this paper, three new species of Nasimyia Yang & Yang, 2010, N. eurytarsa sp. nov., N. rozkosnyi sp. nov. and N. elongoverpa sp. nov. from the Oriental region are described and illustrated; N. nigripennis Yang & Yang, 2010 is found to be a junior synonym of N. megacephala Yang & Yang, 2010 (syn. nov.). Chelonomima signata de Meijere 1924 is combined as Pseudomeristomerinx signata (de Meijere, 1924) comb. nov.. Keys to the Oriental genera of Pachygasterinae with elongate abdomens and the species of Nasimyia are provided, as well as distribution maps of the four species of Nasimyia.